2013
DOI: 10.1523/jneurosci.2001-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hormone Loss Impairs Excitatory Synaptic Transmission at Hippocampal CA3–CA1 Synapses

Abstract: Premature and long-term ovarian hormone loss following ovariectomy (OVX) is associated with cognitive impairment. This condition is prevented by estradiol (E 2 ) therapy when initiated shortly following OVX but not after substantial delay. To determine whether these clinical findings are correlated with changes in synaptic functions, we used adult OVX rats to evaluate the consequences of short-term (7-10 d, OVX Control ) and long-term (ϳ5 months, OVX LT ) ovarian hormone loss, as well as subsequent in vivo E 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In aged OVX rats, the duration of ovarian hormone deprivation dictates whether E2 replacement will be beneficial for hippocampal spine density, synaptic physiology, and learning, supporting the critical window hypothesis (Bohacek and Daniel, 2010, Daniel, et al, 2006a, Gibbs, 2000, Gibbs, et al, 2009, Savonenko and Markowska, 2003, Smith, et al, 2010, Wu, et al, 2013). We previously reported that up to 15 months post-OVX, E2 replacement is capable of increasing CA1 dendritic spine density, GluN2B-mediated transmission, NMDAR/AMPAR ratio, and LTP similar to that in young adult OVX rats following a 2 week deprivation (Smith and McMahon, 2005, Smith and McMahon, 2006, Smith, et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…In aged OVX rats, the duration of ovarian hormone deprivation dictates whether E2 replacement will be beneficial for hippocampal spine density, synaptic physiology, and learning, supporting the critical window hypothesis (Bohacek and Daniel, 2010, Daniel, et al, 2006a, Gibbs, 2000, Gibbs, et al, 2009, Savonenko and Markowska, 2003, Smith, et al, 2010, Wu, et al, 2013). We previously reported that up to 15 months post-OVX, E2 replacement is capable of increasing CA1 dendritic spine density, GluN2B-mediated transmission, NMDAR/AMPAR ratio, and LTP similar to that in young adult OVX rats following a 2 week deprivation (Smith and McMahon, 2005, Smith and McMahon, 2006, Smith, et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…Much of the published physiological research with female rats involves ovariectomized subjects. Ovarian hormone loss results in rapid progressive loss of CA3–CA1 synaptic transmission [ 66 ], so estradiol administration is a common corrective. Unfortunately, despite noncyclic estradiol treatment, many studies report timing-, concentration-, and/or subject-dependent effects [ 67 ], i.e., increased variability in females that does not improve experimental clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal slices were visualized using a fixed-stage upright microscope (Leica Biosystems) equipped with infrared differential interference contrast optics. The recording chamber was continuously superfused with ACSF containing SR95531 (2 mM) and CGP55845 (1 mM) to block inhibitory synaptic transmission and flowing at 1-2 ml/min as we previously described (31)(32)(33). Both recording and stimulating electrodes were pulled from filamented borosilicate pipettes (BF150-86-10; Sutter Instrument, Novato, CA, USA) and filled with ACSF with tip resistance of 1 and 0.7 MV, respectively.…”
Section: Electrophysiology Recordingsmentioning
confidence: 99%